2020
DOI: 10.15835/nbha48111828
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest antimicrobial treatments with organic acids to improve the shelf life of fresh blueberries

Abstract: Fresh highbush blueberries (Vaccinium corymbosum L.) are one of the most popular soft fruits characterized by attractive sensorial attributes and high antioxidant potential. They are highly perishable as they are susceptible to various microbial infections, both pre- and postharvest. The present research was conducted to investigate the effects of postharvest treatments with citric (2%), benzoic (0.2%) and sorbic (0.2%) acids on physicochemical, biochemical and microbiological evolution of fresh blueberries un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Benzoic acid, chlorine dioxide, and 1-methylcyclopropene (1-MCP) are commonly used to prolong the shelf life of postharvest fruit and vegetables [ 11 , 12 , 13 ]. It is reported that preharvest application of benzoic acid can increase the content of total phenolic compounds and total anthocyanins in table grapes [ 14 ], and postharvest antimicrobial treatments with benzoic acid can improve the shelf life of fresh blueberries [ 15 ]. Chlorine dioxide can control postharvest anthracnose disease in mango [ 16 ], and delays the reddening of postharvest green peppers by affecting the chlorophyll degradation and carotenoid synthesis pathways [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benzoic acid, chlorine dioxide, and 1-methylcyclopropene (1-MCP) are commonly used to prolong the shelf life of postharvest fruit and vegetables [ 11 , 12 , 13 ]. It is reported that preharvest application of benzoic acid can increase the content of total phenolic compounds and total anthocyanins in table grapes [ 14 ], and postharvest antimicrobial treatments with benzoic acid can improve the shelf life of fresh blueberries [ 15 ]. Chlorine dioxide can control postharvest anthracnose disease in mango [ 16 ], and delays the reddening of postharvest green peppers by affecting the chlorophyll degradation and carotenoid synthesis pathways [ 17 ].…”
Section: Introductionmentioning
confidence: 99%